Don't be a bully, Billy : a cautionary tale - Cox, Phil Roxbee; McCafferty, Jan; Tyler, Jenny (Tulsa, Okla. : Usborne, 2004)
Little Billy enjoys shoving people around at school, but he soon pays a big price for being a bully.
2.2
K-3
Keywords: Bullying -- Juvenile fiction; Conduct of life -- Juvenile fiction; Behavior -- Fiction; Bullies -- Fiction; Bullies -- Fiction; Human behavior -- Fiction